PENGARUH LINGKUNGAN KELUARGA DAN LINGKUNGAN SEKOLAH TERHADAP MOTIVASI BERPRESTASI SISWA SMA NEGERI 4 MANDAU - Vebby Novisanelli; Suarman Suarman; Mujiono Mujiono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the effect of family and school environment on the achievement motivation of SMA 4 Mandau. The population of this study was 407 students of grade XI of SMA Negeri 4 Mandau, in this study using a simple random sampling technique which required the data taken of 80 class XI students. To get the data needed is a questionnaire method and the previous research was taken to test the validity and reliability. The data analysis technique used is multiple linear regression. The results showed that the family environment and the school environment both partially and simultaneously affect the achievement motivation which means that the family environment and the school environment are included in both categories in learning and have the desire of students to achieve high achievement. Suggestions for schools should strive to provide good facilities because with the convenient facilities it will increase the motivation of student achievement, for students more concerned with the learning process the material delivered is more digestible in order to develop their motivation in learning at school, for researchers to be able to test other variables that can affect achievement motivation.Key Words: Family Environment, School Environment, and Achievement Motivation